Financial inclusion, a driver of state building in India and Mexico? - Cyril Fouillet; Solène Morvant-Roux (Revue Internationale de Politique de Développement)
Since the 1990s, microfinance has become a central element in international development policies, focusing in particular on market building, and mainly driven by private financial players. The end of the 2000s, however, was marked by a return of state legitimacy, through policies and strategies of financial inclusion. Government intervention is motivated by the persistence of social, gender or geographical inequalities. In this perspective, financial inclusion can be a tool for establishing, reforming and strengthening state institutions. In this article, we will situate these latest trends within the evolution of Indian and Mexican social policies. Our argument is that the deployment of financial inclusion policies in these two countries can lead to ambiguous effects. On the one hand, these financial inclusion policies allow vulnerable populations to access new rights, and promote embryonic forms of citizenship. On the other hand, these policies may encourage the emergence of new ways of controlling the behaviour of beneficiary populations.